Intensification of the combustion process in a gasoline engine by adding a hydrogen-containing gas. (16th August 2018) - Gutarevych, Yuriy; Shuba, Yevheniy; Matijošius, Jonas; Karev, Stanislav; Sokolovskij, Edgar; Rimkus, Alfredas
Abstract: The results of research on the impact of adding a hydrogen-containing gas obtained by water electrolysis to the air charge of a gasoline engine on the combustion process, the indicator values of the work process, fuel-consumption efficiency and environmental performance of the engine are provided in the paper. The indicator tests of the work process of the engine have been carried out and the key data on the indicator values of the work process of a gasoline engine have been calculated on the base of the obtained indicator-diagrams. It was found that adding a hydrogen-containing gas caused shortening of all phases of combustion and an improvement of the indicator values of the engine. If a hydrogen-containing gas is added to the air charge of a gasoline engine, fuel-consumption efficiency as well as its energy and environmental performance are improved. Highlights: The fuel consumption decreases adding a hydrogen-containing gas to air charge of a gasolinepowered engine. The maximum temperature of the cycle increases while an engine operates on gasoline with a hydrogen-containing gas. The using of HHO in SI engine decreases the CO and CmHn pollution in the exhaust.